2022
DOI: 10.7717/peerj.13959
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge and barriers of influenza vaccine uptake among university students in Saudi Arabia; a cross-sectional analysis

Abstract: Background Influenza vaccine hesitancy is a significant threat to global maneuvers for reducing the burden of seasonal and pandemic influenza. This study estimated the vaccine uptake, barriers, and willingness for influenza vaccines among university students in Saudi Arabia. Methods A cross-sectional survey was conducted among health science (HS) and non-health science (NHS) university students. A 31-item questionnaire was used to ascertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…With respect to vaccination during the year of the research period, significant differences were found between faculties in the present study, with more students from the health sciences having been vaccinated or planning to be vaccinated compared to computer science and management or social sciences students. Similar findings were obtained in previous studies showing that influenza vaccination was more common among medical students than students in other professions [26,34]. This may be because health sciences students often have clinical experience in hospitals and clinics, making them more concerned about the risk of infection.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…With respect to vaccination during the year of the research period, significant differences were found between faculties in the present study, with more students from the health sciences having been vaccinated or planning to be vaccinated compared to computer science and management or social sciences students. Similar findings were obtained in previous studies showing that influenza vaccination was more common among medical students than students in other professions [26,34]. This may be because health sciences students often have clinical experience in hospitals and clinics, making them more concerned about the risk of infection.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings have been reported in other studies that included students from various fields. For example, a study conducted in Saudi Arabia found that health sciences students had more positive vaccination intentions, consistent with lower hesitancy rates compared to students from other study areas [34]. Based on the research literature, vaccine hesitancy is ultimately reflected in the vaccination rate.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This very low value underlined that public health interventions at the provider and healthcare system level are needed to educate providers on the importance of recommending the vaccine to this hard-to-reach group of people. Furthermore, previous research has clearly shown a significant positive influence of receiving a vaccination recommendation by healthcare professionals in individual decision-making regarding the uptake [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Herzallah et al [13] found that influenza A H1N1 infection was more common in younger age groups and more severe among pregnant women in Eastern Saudi Arabian hospitals. Multiple studies analyzed the prevalence of A(H1N1) infection [17][18][19] and vaccination coverage [24][25][26] in different regions of Saudi Arabia, showing various infection characteristics and uptake rates among different age groups.…”
Section: Literature Reviewmentioning
confidence: 99%